A case of mistaken diagnoses: diagnostic and management challenges in a case of adult autism spectrum disorder. (14th September 2022) - Alexander, L.; Farrelly, N.
Abstract : Autism spectrum disorder (ASD) is frequently identified in children but is often unrecognised in adults. ASD is characterised by difficulties in social interaction, communication and restricted interests, but other presentations are common, especially in adults. This report describes a 34-year-old man with a history of multiple psychiatric diagnoses including generalised anxiety disorder, major depressive disorder and panic disorder. He was diagnosed with ASD in his early 30s and engaged in a targeted treatment plan, including rationalisation of medications, supportive therapy and occupational therapy, which successfully facilitated discharge from mental health services. This case illustrates the atypical presentation of ASD in adults, which is diagnostically challenging. Such cases often present to community mental health services and may be misdiagnosed as treatment resistant cases of depressive, anxiety or personality disorders. Accurate diagnosis and targeted management is more likely to yield a successful outcome.